If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 1 = 3y Reorder the terms: 1 + 4x = 3y Solving 1 + 4x = 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = -1 + 3y Combine like terms: 1 + -1 = 0 0 + 4x = -1 + 3y 4x = -1 + 3y Divide each side by '4'. x = -0.25 + 0.75y Simplifying x = -0.25 + 0.75y
| z-3.6%0.2=-13 | | 3(2X-1)=9(9x+3) | | 2x-3x+5x=20+12 | | -0.5+5= | | 5(a+3)=11a+14-5a | | 19-g/36=10 | | 12-9x-10=22+3x | | (3v-1)(3-v)=0 | | 4(x+2)=25 | | [4x]=32 | | 6=z-[-5] | | 5=1+4n-4 | | -2(r+5)=8-6r+2r | | 3p+4(7-5p)=-35-8p | | Ia+bI=3 | | 4x-5/2x= | | x+2(5x-2)=9-1x | | 81^(1/2) | | 364=8(8-8a)+4a | | 69=-6p-9 | | (sinx)(cosx)=0 | | 1-5p+p-3=-2(p-4)-(6p+6) | | 0.03(10-x)+0.3x=0.05(40) | | 3b-5(b+3)=-11 | | 2m=200cm | | 6x^2+25=100 | | 7+3*4= | | 7+4+(-8)= | | 3x+12=12x+22 | | 2x+1.67x=44 | | 3v^2-4v-4= | | 2x+1.67x= |